2017
DOI: 10.18632/oncotarget.15337
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent gene alterations with EGFR mutation and treatment efficacy of EGFR-TKIs in Chinese patients with non-small cell lung cancer

Abstract: PurposeWe investigated the frequency of concurrent genes in EGFR-mutant non-small cell lung cancer patients and determined its value in predicting the efficacy of EGFR-TKIs treatment.MethodsThree hundred and twenty patients, who harbored EGFR activating mutations and received EGFR-TKIs treatment, were examined for another eight genes including KRAS, NRAS, PIK3CA, BRAF, and HER2 mutations and ALK, ROS1, and RET fusion genes based on reverse transcription PCR. Progression-free survival and overall survival with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 31 publications
6
26
1
Order By: Relevance
“…Rare mutations, such as the HER2 mutation and MET exon 14 skipping, can co‐occur with EGFR mutations, and patients with these types of coalteration have been reported to respond well to EGFR‐TKI or combined therapy . In our center, patients first diagnosed with NSCLC were routinely screened for EGFR , ALK , ROS1 , KRAS , and BRAF alterations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rare mutations, such as the HER2 mutation and MET exon 14 skipping, can co‐occur with EGFR mutations, and patients with these types of coalteration have been reported to respond well to EGFR‐TKI or combined therapy . In our center, patients first diagnosed with NSCLC were routinely screened for EGFR , ALK , ROS1 , KRAS , and BRAF alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant driver gene mutations in EGFR and ALK have been detected in 1.3%‐15.4% of the patients with non‐small cell lung cancer (NSCLC), depending on the method used . Among the patients harboring EGFR / ALK coalterations, some responded to treatment with an EGFR‐TKI (ie, gefitinib, erlotinib, icotinib, or afatinib), while others responded to treatment with an ALK‐TKI (crizotinib) or both . To the best of our knowledge, there is currently no consensus for the optimal management for these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NSCLC, oncogenic driver mutations are typically mutually exclusive, although cases of mutations in multiple driver genes are increasingly reported [5,[7][8][9][10][11][12][13][14]. EGFR/KRAS co-mutation is likely to represent a certain proportion of cases of multiple mutations in NSCLC [12].…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC prior to treatment, the majority of oncogenic driver mutations are mutually exclusive with other mutations [5,6]. However, recent studies have shown that additional driver mutations such as KRAS, ALK, and PI3K mutations co-exist with EGFR-mutations in a certain percentage of lung cancers [5,[7][8][9][10][11][12][13][14]. Of note, these driver mutations have been found not only in different cell populations in tumors, but also within the same cell population [15,16].…”
Section: Introductionmentioning
confidence: 99%